The productive online and offline professor : a practical guide - Stachowiak, Bonni Jean, 1971- (Thrive Online Seriesis Focused on the Needs, Interests, and the Best Practices of Online Educators with the Ultimate Goal of Helping Them to Better Serve Online Students. the Contributors to the Thrive Online Seriesare Fearless, Committed Thought Lead., 2020)
"The Productive Online Professor assists those who teach online and blended courses with managing their personal productivity. Faculty are often expected to provide support and feedback to learners outside of normal work hours in non-traditional classes. Programs that are designed with more asynchronous content may cause faculty to perceive that it is difficult to ever press the "off button"on their teaching.The author offers guidance and suggests software tools for streamlining communication and productivity that enable faculty to better balance their lives while giving rich feedback to students. Part 1 addresses the challenges in defining productivity and presents a working definition for the text. Part 2 describes the ability to communicate using both synchronous and asynchronous methods, along with ways of enriching such communication. Part 3 describes methods for finding, curating, and sharing relevant knowledge both within one's courses and to a broader personal learning network (PLN). Part 4 examines specific tools for navigating the unique challenges of productivity while teaching online. It includes ways to grade more productively while still providing rich feedback to students. Part 5 shares techniques for keeping one's course materials current and relevant in the most efficient ways possible. The Productive Online Professor is a practical guide for how to provide high quality online classes to diverse students. This book shares specific technology and other tools that may be used in charting a course toward greater productivity. It is intended to be a professional resource for fulfilling our roles with excellence and joy, while managing other priorities in our personal and professional lives"--